Comparison of plantar loads among runners with different strike patterns - Wei, Z.; Zhang, Z.; Jiang, J.; Zhang, Y.; Wang, L. (Journal of Sports Sciences, 2019)
This study aimed to explore the plantar loading variables between habitual rearfoot strike (RFS) and non-rearfoot strike (NRFS) during running. 78 healthy males participated in this study (41 RFS, 37 NRFS). In-shoe pressure sensors were used to measure plantar loading while the participants were running on a 15 m indoor runway with their preferred foot strike pattern (FSP) at 12.0 ± 5% km/h. Results indicate that force and pressure parameters were much higher in the rearfoot and midfoot regions during RFS running and relatively greater in forefoot region during NRFS running. However, compared with NRFS running, the contact area, maximum force and force-time-integrals during RFS running on total foot were 21.44% (P < 0.001, ES = 2.29), 13.99% (P = 0.006, ES = 0.64) and 21.27% (P < 0.001, ES = 0.85) higher, respectively. Total foot peak pressure and pressure-time-integral between two FSPs were similar. Higher loads in the rearfoot region may transmit to the knee joint and result in patellofemoral joint injuries. NRFS runners` higher loads in forefoot seem to be ralated to metatarsal stress fractures and compensatory damage to the Achilles tendon. Therefore, runners should choose proper FSPs according to their unique physical conditions.